THE INFLUENCE OF ANIMALIA LEARNING DESIGN WITH EXPERIENTIAL MODEL TO SCHOOL’S SURROUNDING ENVIRONMENT - Nisa, Aulia Zulfatu; Alimah, Siti; Marianti, Aditya (Unnes Science Education Journal, 2017)
Abstract ___________________________________________________________________ This research aims to determine the effect of applied animalia learning design with the model of experiential jelajah alam sekitar* on learning outcomes and activities of students class X MIPA in senior high school 1 Ungaran. This research is quasi experimental design and it using posttest only control group design. Sample of this research were class X MIPA 6 (experimental class) and X MIPA 7 (control class), taken by cluster random sampling. Independent variabel in this research is learning design with EJAS model on the topic of animalia, while depends variabel is learning outcomes and students activities. The result of t-test showed that mean posttest value of experimental class is higher than control class, with clasical completeness 92% (KKM ≥ 75). Based on the result the experimental class students activities analysis showed that highest activity is motor activities (92.35%), writing activities (92.12%), cooperation activities (91.90%), analysis avtivities (82.40%), and oral avtivities (80.20%) . In general, teacher and students gave a positive response to applied learning. Conclusion from this research is applied animalia learning design with EJAS model positive effect on learning outcomes and student’s activities.